Etnis Kurdi Iran dan Revolusi Islam 1979 M - Faiz Nasrullah (JUSPI (Jurnal Sejarah Peradaban Islam), 2020)
The politics of discrimination applied by the Iranian government both politically and religiously became the beginning of the emergence of the Kurdish resistance movement towards political policies, one of which resistance arose after the 1979 Iranian revolution. This writing aims to analyze the ethnic conditions of Iran's Kurds after the 1979 Iranian Revolution. Historical methods, Political approach as well as descriptive-analysis can be concluded that the existence of the Iranian revolution did indeed result in victory in the struggle against the Shah Reza Pahlevi regime and carried Islamic symbols. However, in reality the victory brought a separate problem for the early administration in Iran due to the emergence of several ethnic communities in the Iranian region who wanted a concession in the form of cultural autonomy and political concessions on the national scene.